Pengaruh Pemanfaatan Hasil Limbah Cair Tahu Fermentasi Terhadap Kelulushidupan dan Pertumbuhan Ikan Puyu (Anabas testudineus) - Fakhrunnas MA Jabbar; T Iskandar Johan; Muhammad Hasby; Hisra Melati; Safitriani Safitriani (Dinamika Lingkungan Indonesia, 2023)
Climbing perch (Anabas testudineus) is one type of swamp fish that has the potential to be cultivated. The obstacle faced in the development of quail aquaculture is its slow growth because it takes 6-7 months to reach a length of 8-10 cm and a weight of 15-16 grams. The food for quail is usually eaten by aquatic plants such as water lettuce (Pistia stratiotes), weeds, other small animals, and insects. Feed is one of the main factors that can support fish breeding. As a place for fish to live, water quality is strongly influenced by physical and chemical factors of water such as temperature, dissolved oxygen, pH, ammonia, nitrite, and nitrate. Because the use of freshwater media added with salt has several advantages, it can inhibit the growth of fungi and increase antibodies against disease attacks. The objectives and plans of this research are. To determine the effect of different doses of maintenance media on the spawning of quail (A. testudieneus Bloch). Morever, to find out and provide the best optimal dose for rearing quail (A. testudieneus Bloch). It find out the best dose for spawning quail (A. testudieneus Bloch). It be used as a reference for further research ?. Hopefully, this study can provide benefits and insights for the cultivation technology of quail (A. testudieneus Bloch) either continuously or in a way that is good for its living media.